Application of Ultrasonic Technology for Water and Wastewater Treatment - AH Mahvi (Tehran University of Medical Sciences, 2009)
Ultrasonic technology as an innovative technology may be used for water and wastewater treatment for pollution removal. This technology acts as an advanced oxidation process. Application of this technology leads to the decomposition of many complex organic compounds to much simpler compounds during physical and chemical compounds during cavitation process. In this article review, some applications of this valuable technology are presented.